Desenvolvimento de metódo voltamétrico para determinação de carbendazim em águas de rio e estudo de viabilidade econômica para monitoramento ambiental - Lima, Maria Clara Rodrigues de (2022)
Scientific studies around the world have been developed to reduce and prevent the pollution of water bodies and provide an increase in the efficiency of monitoring of contaminants in these waters. Pesticides have attracted the attention of researchers in various aspects, such as the control of contamination levels at trace levels of these compounds in different environmental matrices. In this sense, voltammetry gains space due to its high sensitivity, high selectivity, versatility, practicality and low cost. In this study, the objective is to develop a voltammetric method for detection and determination of the pesticide Carbendazim (CAR), as well as to study the economic viability to apply it as a method of analysis by Organs environmental agencies of the State of Paraíba. The electroactivity of CAR was investigated from Cyclic Voltammetry experiments using a sweep speed (v) of 100 mV s–1. For Differential Pulse Voltammetry, a pulse amplitude (a) of 25 mV, a modulation time (tm) of 70 ms, a potential increment (ΔEs) of 2 mV and a v of 5 mV s-1. The optimization of the parameters of the determination method was performed by full factorial design 23, the variables involved were tm, a and v. The proposed method was applied to analyzes of river and drinking water samples. The precision of the method was evaluated in terms of repeatability and reproducibility and acceptable values of rsd below 5% were found (5.5 × 10-6 mol L–1 CAR solution). The dynamic linear range obtained was from 9.9 × 10-7 to 4.5 × 10-5 mol L-1, with detection limit (LD) of 3.9 × 10-7 mol L-1 (74.9 μg L-1), proving to be an excellent value because it is much lower than that practiced by Brazilian legislation. The technique developed was evaluated to the detriment of its economic, technical and environmental feasibility, showing itself to be promising and considerably advantageous in all these aspects. The economic feasibility was analyzed based on the cash flow model, with the help of Net Present Value (NPV), Internal Rate of Return (IRR), Cost-Benefit Ratio and Discounted Payback Period. The results obtained were encouraging, with a positive NPV of R$ 228,087.59 in the first year of implementation of the method, in addition to a discounted payback period equal to 10 months and 18 days and an IRR in the first year of 1193.02%. Such results assume that the method, in addition to being viable and sustainable, is profitable, contributing to savings of R$ 5,540,631.20 in a period of 20 years and being able to generate millionaire revenues through the provision of private services with prices of highly competitive analyses. In addition, the voltammetric technique promotes, in 20 years, a reduction in the consumption of H2SO4 (99.84%), NaOH (99.77%) and CAR (85.00%), respectively. Eliminating, in these 20 years, the use of organic solvents used in chromatographic techniques, for example: methylene chloride, acetone, methanol and hexane, with a reduction equivalent to 4,231.72 liters of reagent and consequently of chemical residues.